The Manly Priest : Clerical Celibacy, Masculinity, and Reform in England and Normandy, 166-13 - Thibodeaux, Jennifer D. (Book collections on Project MUSE., 2015)
The Manly Priest examines the clerical celibacy movement in medieval England and Normandy, which produced a new model of religious masculinity for the priesthood and resulted in social tension and conflict as traditional norms of masculine behavior were radically altered for this group of men.